Evaluación toxicológica del río Minas, parroquia Piartal, cantón Montúfar - Hernández Erazo, Leydi Dayanara (2023)
Since it performs crucial environmental tasks like participating in chemical processes, controlling temperature, delivering nutrients, and promoting both social and environmental growth, water is crucial to the existence of life. This study examined the Minas River's water quality and toxicity index, which is a part of the Piartal parish in the Carchi province. A bioassay using Lactuca sativa L lettuce was conducted, and the results showed a low water quality index with a bad classification of 45 despite the fact that no previous water quality studies had been carried out in the area value that is in the range 26 to 45. Additionally, the results of the bioassay showed that the water is not toxic for the germination and growth of the plants. On the other hand, the toxi-chrom test revealed that all the water samples analyzed are toxic, exceeding the 50% threshold in the interpretation of results, the microbiological analyses showed a significant growth of bacteria, which influences the determination of water quality. The extensive agricultural and animal activities in the research area may be to blame for the negative consequences that have been seen in the water quality of the Minas River, which is classed as poor. As a result, it is advised that soil analyses be carried out in the river's vicinity to gather information on the physical, chemical, and microbiological traits that will help explain the poor water quality of the Minas River inside the Piartal parish line.